HIV-1 Nef disrupts CD4+ T lymphocyte polarity, extravasation, and homing to lymph nodes via its nef-associated kinase complex interface - Lamas Murua, Miguel; Stolp-Rastätter, Bettina; Kaw, Sheetal; Thoma, Judith; Tsopoulidis, Nikolaos; Trautz, Birthe; Ambiel, Ina; Reif, Tatjana; Arora, Sakshi; Imle, Andrea; Tibroni, Nadine; Tanaka, Motomu; et al. (The journal of immunology, 2018)
HIV-1 Nef is a multifunctional protein that optimizes virus spread and promotes immune evasion of infected cells to accelerate disease progression in AIDS patients. As one of its activities, Nef reduces the motility of infected CD4+ T lymphocytes in confined space. In vivo, Nef restricts T lymphocyte homing to lymph nodes as it reduces the ability for extravasation at the diapedesis step. Effects of Nef on T lymphocyte motility are typically mediated by its ability to reduce actin remodeling. However, interference with diapedesis does not depend on residues in Nef required for inhibition of host cell actin dynamics. In search for an alternative mechanism by which Nef could alter T lymphocyte extravasation, we noted that the viral protein interferes with the polarization of primary human CD4+ T lymphocytes upon infection with HIV-1. Expression of Nef alone is sufficient to disrupt T cell polarization, and this effect is conserved among lentiviral Nef proteins. Nef acts by arresting the oscillation of CD4+ T cells between polarized and nonpolarized morphologies. Mapping studies identified the binding site for the Nef-associated kinase complex (NAKC) as critical determinant of this Nef activity and a NAKC-binding-deficient Nef variant fails to impair CD4+ T lymphocyte extravasation and homing to lymph nodes. These results thus imply the disruption of T lymphocyte polarity via its NAKC binding site as a novel mechanism by which lentiviral Nef proteins alter T lymphocyte migration in vivo.
Gesehen am 04.11.2019